1996
DOI: 10.1039/ft9969205013
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal copolymer microgels of N-isopropylacrylamide and acrylic acid: pH, ionic strength and temperature effects

Abstract: Aqueous colloidal microgels have been prepared, based on poly(N-isopropylacrylamide) [poly(NIPAM)], cross-linked with bisacrylamide, containing 5% w/w acrylic acid (AAc) as a comonomer. Transmission electron micrographs of the microgels show that the copolymer microgels are monodisperse spheres. The size of the microgel particles containing 5% AAc has been studied, using dynamic light scattering, as a function of pH (3-lo), ionic strength (10-4-10-' M NaC1) and temperature (20-75°C). The hydrodynamic diameter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
249
0
9

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(271 citation statements)
references
References 7 publications
13
249
0
9
Order By: Relevance
“…However, the poly(NIPAM-AA) hydrogel is weakly hydrated due to the hydrophilicity of the NIPAM moieties. 18 As the pH increases, the acrylic acid moieties begin to deprotonate, generating electrostatic repulsion within the polymer network thus causing it to swell with water. A steep increase in the diameter of the particles occurs near the pk a of acrylic acid between a pH of 4.3 to 4.7.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the poly(NIPAM-AA) hydrogel is weakly hydrated due to the hydrophilicity of the NIPAM moieties. 18 As the pH increases, the acrylic acid moieties begin to deprotonate, generating electrostatic repulsion within the polymer network thus causing it to swell with water. A steep increase in the diameter of the particles occurs near the pk a of acrylic acid between a pH of 4.3 to 4.7.…”
Section: Resultsmentioning
confidence: 99%
“…14 Other recent studies reported that relaxivity values are nearly independent of polymer coatings for large magnetic particles (100 nm), while the relaxation rates of smaller particles (10 nm) were dramatically reduced when coated with silica. 18,19 Another report showed that increasing the hydrophilicity of the particle coating leads to enhanced interactions between the protons with the magnetic core thereby increasing the relaxivity. 13 Recently, Monte Carlo simulations illustrated that some of these discrepancies in effects are attributed to differences in particle size (or dephasing mechanism) and coating composition.…”
Section: 811à16mentioning
confidence: 99%
See 1 more Smart Citation
“…This decreases the space between them, ejecting solvent and losing volume. The temperature at which this occurs may be adjusted by the temperature of processing [145], blending [146] and microstructure [147], in addition to the inclusion of composites which may adjust temperature response through density changes [148], or Joule or surface plasmon resonance heating (see later sections on light, electricity and magnetism for these mechanisms).…”
Section: Heatmentioning
confidence: 99%
“…The codes and detail ingredient of the NIPAAm-AA nanoparticles was shown in Table . From Table , high conversion (>95%) of all the linear polymers (data not shown) and nanoparticles were measured. In typical free radical polymerization reaction, high conversion (>90%) are easily achieved within two hours [15,18]. The transmission electron micrograph of the LPIA5 nanoparticle was shown in Figure 1.…”
Section: Synthesis Of Nipaam-co-aa Polymers and Nanoparticlesmentioning
confidence: 99%